Advance-Platelet Rich Fibrin and Hyaluronic Acid Combination Improves Interleukin-6 and Granulation Index in Diabetic Foot Ulcer Patients - Ronald Winardi Kartika; Idrus Alwi; Franciscus Dhyanagiri Suyatna; Em Yunir; Sarwono Waspadji; Suzanna Immanuel; Todung Silalahi; Saleha Sungkar; Jusuf Rachmat; Saptawati Bardosono; Mirta Hediyati Reksodiputro (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Diabetic foot ulcer (DFU) is the most common and threatening complication of Diabetes Mellitus (DM). Ideal wound dressing for DFU management should relieve symptoms, provide wound protection, and encourage healing. Advanced-Platelet Rich Fibrin (A-PRF) and Hyaluronic Acid (HA) have been proven to improve wound healing process. This study was aimed to demonstrate the ability of combination of A-PRF and HA in reducing inflammation and improving DFU tissue healing.METHODS: Twenty DFU subjects were involved in this study, and divided into two groups based on the topical fibrin gel treatment: A-PRF + HA group and A-PRF only group. A-PRF was obtained by peripheral blood centrifugation. A-PRF + HA was prepared by homogening A-PRF and AH with a ratio of 1:0.6. Interleukin-6 (IL-6) level, granulation index (GI), numeric pain score (NPS), and inflammation clinical symptoms (ICS) were assessed on day-0, 3, 7 and 14.RESULTS: Wound swabs’ IL-6 level on day-7 was found to be significantly lower in A-PRF + HA compared to A-PRF alone (p=0.041). The IL-6 level reduction also found to be significant higher either in wound swabs (day 0-7, p=0.015) or fibrin gel (day 0-3, p=0.049; day 0-7, p=0.034). A-PRF + HA treatment significantly increased the GI even since day-3 (p=0.043), with lower NPS (p<0.001), and ICS score.CONCLUSION: The combination of A-PRF and HA increases the GI in DFU healing by reducing the inflammation state which will induce the angiogenesis process, as well as reducing pain in DFU subjects better than A-PRF alone.KEYWORDS: inflammation, interleukin-6, wound healing, angiogenesis, proliferation